ANALISIS CASH FLOW RATIO UNTUK MENGUKUR KINERJA KEUANGAN SERTA NILAI PERUSAHAAN INDUSTRI (STUDI KASUS PT XYZ) - SAFRI SAFRI (JURNAL TEKNIK INDUSTRI, 2018)
The results indicate the ability of PT XYZ to fulfill short-term obligations on time, Efficiency Ratio with interpretation that efficient management in managing company cash, from investment and funding ratio, company need to consider to buy new fixed asset, because investment ratio implies fixed asset cost of company , A ratio of current liabilities of 2.2 times and a cash debt of 1.7 times indicates that firms use more of their own capital compared with long-term debt utilization, the amount of their own capital use and reduced debt in meeting the operational needs of the company may result in reduced savings benefits taxes from the use of debt Based on the comparative analysis of company value can be seen that the value of the company PT. XYZ of 23.77 highest in the parameters of 2013 until 2016. Increase in the value of the company in the year in line with the optimization of the company's capital structure because the company's value will be optimal if the minimum capital cost of the companyKeywords: Cashflow, Ratio.